Peran Akun Tiktok Sebagai Sarana Penyuluhan Pajak Dalam Rangka Meningkatkan Kesadaran Pajak Pelaku UMKM - Liyana, Nur Farida; Sulastri, Heni (Politeknik Keuangan Negara STAN, 2023)
Given the large role of tax and MSMEs in the Indonesian economy, efforts to increase tax awareness among MSMEs are urgently needed. In 2021, TikTok account users in Indonesia reached 99.1 million people, the second largest in the world. With such a large number of users, this study aims to find out the role of the TikTok platform as a tax dissemination tools for increasing tax awareness among MSME’s. This study uses a descriptive research method with a qualitative approach. The results of this study indicate that the use of TikTok plays an important role in increasing tax awareness. Through the official TikTok account of the Directorate General of Taxes (DGT), various information related to taxation is easier, faster, cheaper, and more extensive to reach MSME actors throughout Indonesia. DGT should produce more innovative and interesting content more frequent and consistent for uploading videos, and use the TikTok paid advertising facility (TikTok ads) in order to educate society to increase tax awareness. In addition, collaboration with tax dissemination content creator specialist is another choice to make tax dissemination through TikTok platform play a big role and have an impact on tax awareness.